Envelhecer dançando: a dança tradicional gaúcha em grupos xirus de Santa Maria/RS - Freitas, Bruna de Bragas (2023)
This is a qualitative ethnographic research (MINAYO, 2014; MAGNANI, 2002) on the body and emotional perception of subject-dancers of xirus winter festivals in the city of Santa Maria/RS from their aging process (GOLDENBERG, 2022; NERI, 2008) in Gaucho Traditional Dance groups. Two xirus groups were analyzed, with 28 subjects. And by understanding the traditionalism of Rio Grande do Sul (LESSA, 1984; CÔRTES, 1981; CAMILO, PEREIRA, 2013) as cultural interference in aging, this investigation is relevant due to the scarce studies thought from the chosen target audience, added to the impact of dance with a motivating and socializing function for the older subject. The way was given in the identification of the groups of the city, and their dancers, of the analysis of the relation of the Traditional Dances with the active aging (OMS, 2005; CHECOM, GOMES, 2015), and of the understanding of the subjects about their aging process by exploring the gender difference between pawns and gifts (SCOTT, 1989; LOURO, 2003). To carry out this research, theoretical references relevant to the theme and data collection were addressed, which took place from a questionnaire (LAGER apud LIMA, 2016; CASTRO, 2020), an interview (GIL, 2010) and observations recorded in a field diary (WINKIN, 1998). Subsequently, the data was analyzed (BARDIN, 2016) from categories, which were created with information supported by the information collection tools. Some stereotypes with gender issues were perceived, however there is a transformation of thoughts and behaviors regarding aging. Despite the presence of perspectives of losses and declines, most of the collaborators face the aging process in a free and coherent way, not being perceived denial or rejection with/by this phase of life. There are poems in the aging of those who dance.